Studi Efektivitas Vaksin Influenza: Updated Review - Abednego Kristande Gwiharto; Cecep Suhandi; Cheryl Alodya; Rano K. Sinurya (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—Influenza is caused by a rapidly mutating virus that consists of 2 types, namely, type A with the H1N1 and H3N2 genotypes and type B. Influenza caused global mortality with 250,000-500,000 death in 2009. The effectiveness of vaccines also changes regarding the mutation of influenza viruses, however, the development and utilization of influenza vaccines should be supported by the economic status of a country. Up to now, many countries have not prioritized the utilization of influenza vaccines. The target of influenza vaccination in children and adults (> 60 years old). The purpose of this review was to determine the effectiveness of influenza vaccines from various countries and categorize them based on their income. This review used Medline, Elsevier, and BMC Public Health as the database with the keywords